PRDM14在非小细胞肺癌中的表达及其与临床病理因素的关系 (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: The positive regulatory domain proteins (PRDM) are family of transcriptional regulation related to the formation of human tumor factor and play key roles in the cell differentiation and malignant transformation. PRDM14 is a member of the PRDM family. The aim of this study is to detect the expression of PRDM14 in non-small cell lung cancer (NSCLC) tissues, and analyze its relationship with clinicopathologic characteristics of NSCLC. METHODS: PRDM14 expression was detected in 70 NSCLC specimens and 7 paracancerous tissues using the immunohistochemistry (SP method). The PRDM14 protein expression was determined in 42 NSCLC specimens and 42 paracancerous tissues by Western blot. RESULTS: Among 70 NSCLC specimens, 8 specimens showed weak expression of PRDM14 (11.43%, 8/70), 62 specimens showed moderate to strong staining of PRDM14 (88.57%, 62/70), whereas 7 paracancerous specimens showed weak staining extent. PRDM14 expression level was positively correlated with differentiation (P=0.046) and histological type (P=0.047). The positive cytoplasmic expression of PRDM14 in highly differentiated NSCLC, the low expression of PRDM14 in poorly differentiated NSCLC. The results of Western blot showed that there were significant difference between the two groups (P < 0.001); expression of PRDM14 was conspicuous in NSCLC specimens but low in paracancerous tissues. PRDM14 expression level was positively correlated with differentiation (P=0.017). The positive cytoplasmic expression of PRDM14 in highly differentiated NSCLC, the low expression of PRDM14 in poorly differentiated NSCLC. CONCLUSION: The high expression of PRDM14 in NSCLC is associated with differentiation and histological type. The PRDM14 may play an important role in the development of NSCLC.